2017
DOI: 10.1037/pspp0000145
|View full text |Cite
|
Sign up to set email alerts
|

How stable is the personal past? Stability of most important autobiographical memories and life narratives across eight years in a life span sample.

Abstract: Considering life stories as the most individual layer of personality (McAdams, 2013) implies that life stories, similar to personality traits, exhibit some stability throughout life. Although stability of personality traits has been extensively investigated, only little is known about the stability of life stories. We therefore tested the influence of age, of the proportion of normative age-graded life events, and of global text coherence on the stability of the most important memories and of brief entire life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 73 publications
(123 reference statements)
8
54
0
Order By: Relevance
“…This raises the question of whether the selection of specific events included in their life narratives was stable over time. In a recent analysis of this longitudinal data set, Köber and Habermas () reported that roughly 40–60% of the events from the life story were repeated after a 4‐year delay. Given that nearly half of the events in a life story changed across narrations, the evidence of narrative style presented here is not likely due to merely narrating the same events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question of whether the selection of specific events included in their life narratives was stable over time. In a recent analysis of this longitudinal data set, Köber and Habermas () reported that roughly 40–60% of the events from the life story were repeated after a 4‐year delay. Given that nearly half of the events in a life story changed across narrations, the evidence of narrative style presented here is not likely due to merely narrating the same events.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, narrative researchers have started to systematically study consistency, stability, and change in personal narratives in several ways: by examining (a) the selection or deselection of events/details included in repeated tellings of narratives (Bauer, Tasdemir-Ozdes, & Larkina, 2014;K€ ober & Habermas, 2017;Mackinnon, De Pasquale, & Pratt, 2016;McAdams et al, 2006;Strauman, 1996;Thorne, Cutting, & Skaw, 1998), (b) how the meaning or interpretation of events may change (Josselson, 2009), (c) the choice of central themes in the narrative (Dunlop, Guo, & McAdams, 2016;McAdams et al, 2006), and (d) the structure/organization of the narratives as an index of an individual's narrative style (McLean, Pasupathi, Greenhoot, & Fivush, 2017). While prior studies have shown somewhat modest stability in regard to selection of events (Bauer et al, 2014;K€ ober & Habermas, 2017;Mackinnon et al, 2016;McAdams et al, 2006;Strauman, 1996;Thorne et al, 1998), the meaning/interpretation of events (Josselson, 2000) and narrative themes (Dunlop et al, 2016;McAdams et al, 2006;Sengsavang, Pratt, Alisat, & Sadler, 2017) have shown relatively more stability. However, the consistency and stability of narrative organization, as indexed by narrative coherence, are largely unknown.…”
Section: Personality and Narrativementioning
confidence: 99%
“…It is important to note, however, that the years spanning emerging to young adulthood do consist of different changes and life transitions (e.g., marriage, parenthood) that perhaps are more other‐focused than an earlier self‐focused period. At the same time, Köber and Habermas () found stability of life narratives increased between ages 8 and 24, and then leveled off in middle adulthood. In their study, normative life events, such as college, tended to exhibit greater stability compared to other, non‐normative memories.…”
Section: Introductionmentioning
confidence: 94%
“…Rank‐order stability reveals individuals' relative placement over time on levels of personality features, whereas mean‐level change describes normative changes in personality and refers to increases or decreases in the average level of a feature in a population (Roberts, Walton, & Viechtbauer, ). To date, there have only been a few longitudinal studies of life stories over time (e.g., Dunlop, Guo, & McAdams, ; Köber & Habermas, ; Köber, Schmiedek, & Habermas, ; McAdams et al, ; Thorne, Cutting, & Skaw, ), none of which has focused specifically on the transition from emerging to young adulthood. As such, the primary aim of the present study was to examine the rank‐order stability and mean‐level change in narrative identity features during this transition period when the life story is beginning to be coherently crystallized, elaborated, and integrated into the wider personality.…”
Section: Introductionmentioning
confidence: 99%
“… All segments of life narratives were coded for category of event (see Köber & Habermas, , for more detail). For this study, we explored the three most frequent event categories that contained parents' presence by age at time of event, but due to limited space, we describe these results here only summarily.…”
mentioning
confidence: 99%